Lease Farming in Kerala Findings from Micro Level Studies - K\N NAIR, VINEETHA MENON (Economic and Political Weekly June 30, 2006, 2006)
The Land Reforms Act in Kerala rendered tenancy invalid and prohibited the creation of future tenancies in the state. But tenancy still exists. It is a consequence of the simultaneous increase in two categories of people, "those who have land but are unable to cultivate" and "those who have the labour and skills, but have no lands or not enough lands of their own to cultivate". This paper examines some micro level studies on tenancy in Kerala, more specifically, its prevalence across locations and crops, characteristics of lessors and lessees, the terms of lease and the income derived from lease cultivation. It argues for institutionalised arrangements for the expansion of leasecultivation, rather than sterner measures to check it. Among other factors, large-scale entry of self-help groups into the lease market to take up lease cultivation, oftenbringing hitherto fallow lands into production, prompts such a positioning.